Investigating maternal perspectives of breastfeeding support targeted towards fathers in the Milk Man mobile app intervention - White, Becky; Giglia, Roslyn; Burns, Sharyn; Scott, Jane (Springer Nature, 2023)
Background The support of her infant’s father is one of the most important factors influencing a mother’s breastfeeding success, and an increasing number of interventions are targeted towards fathers. Engaging fathers as agents to influence a maternal behavior is potentially problematic, yet few studies report on maternal experiences.